Extension of exton's hypergeometric function \(K_{16}\) - Atash, Ahmed Ali; Kulib, Maisoon Ahmed (CUBO, A Mathematical Journal, 2021)
The purpose of this article is to introduce an extension of Exton's hypergeometric function \(K_{16}\) by using the extended beta function given by OÌˆzergin et al. [11]. Some integral representations, generating functions, recurrence relations, transformation formulas, derivative formula and summation formulas are obtained for this extended function. Some special cases of the main results of this paper are also considered.